PENGEMASAN TARI YAPONG DALAM BENTUK MEDIA AUDIO VISUAL UNTUK SISWA KELAS X - Manalu - Elpriade (Universitas Negeri Medan, 2022)
Abstract - This study aims to describe the packaging steps for Yapong dance in an audio-visual form in accordance with KD 3.1, namely concepts, techniques, and procedures in imitating the basic movements of the Yapong dance and according to KD 4.1, namely imitating the basic dance movements according to the count or beat. The theories used are Setyosari's (2015) theory, namely the steps of audio-visual packaging including planning, preparation, production and evaluation. The theory of product packaging by Senjaya, Wina (2011: 20) is that in packaging content or learning materials into teaching materials, there are considerations such as conformity with the objectives to be achieved, simplicity, elements of message design, material organization, and instructions for use. The learning media method used is descriptive qualitative method. The research instrument used was to use a media validation test questionnaire and a material validation test questionnaire. This research produces audio-visual learning media for Yapong dance material, related to concepts including Yapong dance background, movement terminology, musical instruments, make-up and fashion. Techniques, described through dancekript, and procedures include procedures for Yapong dance movements, and procedures for describing the Yapong dance. The entire research results are packaged in audio-visual form and then validated by material experts and media experts. From the validation 4,7 from material experts and 4,8 from media experts were obtained. From the acquisition of these values indicates that the packaging of the Yapong dance is feasible to be applied as a medium of learning in Senior High Schools.Keywords: Packaging, Yapong Dance, Audio visual Media. Abstrak - Penelitian ini bertujuan untuk mendeskripsikan langkah-langkah pengemasan tari Yapong dalam bentuk audio visual sesuai dengan KD 3.1 yaitu konsep, teknik, dan prosedur dalam menirukan ragam gerak dasar tari Yapong dan sesuai KD 4.1 yaitu menirukan ragam gerak dasar tari sesuai dengan hitungan atau ketukan. Teori – teori yang digunakan adalah Teori Setyosari (2015) yaitu langkah – langkah pengemasan audio visual meliputi perencanaan, penyusunan, produksi dan evaluasi. Teori pengemasan produk oleh Senjaya, Wina (2011: 20) yaitu dalam mengemas isi atau materi pembelajaran menjadi bahan ajar terdapat pertimbangan seperti kesesuaian dengan tujuan yang harus dicapai, kesederhanaan, unsur – unsur desain pesan, pengorganisasian bahan, dan petunjuk cara penggunaan. Metode media pembelajaran yang digunakan adalah metode deskriptif kualitatif. Instrumen penelitian yang digunakan adalah dengan menggunakan angket uji validasi media dan angket uji validasi materi. Penelitian ini menghasilkan media pembelajaran audio visual materi tari Yapong, terkait konsep meliputi latar belakang, terminologi gerak, instrumen musik, tata rias dan tata busana. Teknik, dideskripsikan melalui dancescript , dan prosedur meliputi prosedur ragam gerak tari Yapong, dan uraian tari Yapong. Keseluruhan hasil penelitian yang dikemas dalam bentuk audio visual kemudian divalidasi oleh ahli materi dan ahli media. Dari validasi tersebut diperoleh hasil 4,7 dari ahli materi dan 4,8 dari ahli media. Dari perolehan nilai tersebut mengindikasikan bahwa kemasan tari Yapong layak untuk diterapkan sebagai media pembelajaran di Sekolah Menengah Atas. Kata Kunci: Pengemasan, Tari Yapong, Media Audio visual